Philippine Employment and Industrial Relations Policies: An Assessment - Maria Teresa Sanchez-Robielos; Gonzalo Jurado (Philippine Institute for Development Studies (PIDS), 1998)
Acceleration of economic growth and development, alleviation of poverty and the promotion of greater equity in Philippine society have been the major concerns of Philippine policies and reforms. Key elements to these reforms are employment generation and cooperation in industrial relations. Hence, the government laid down three important documents: the National Employment Plan (NEP) 1993-1998, the Medium Term Philippine Development Plan (MTPDP) 1993-1998 and the Comprehensive Employment Strategy Programs (CESP) 1995. The paper's objective is to assess how far the government has gone in terms of accomplishing employment generation and cooperation in industrial relations. This paper also evaluates the impact of these accomplishments on the national goals of enhanced growth, reduced poverty and improved equity.
Keywords: 330; unemployment; industrial relations; labor migration; income distribution